Eksistensi Kegiatan Keagamaan Islam Aboge pada Masa Pendemi COVID-19 di Kabupaten Probolinggo - Dewi, Khofifah Kurnia; Fauzi, Agus Machfud (Laboratorium Sosiologi FISIP Universitas Jember, 2021)
There are many followers of Aboge Islam (Alip Rebo Wage) in Probolinggo Regency, including the Districts of Leces, Tegalsiwalan, Dringu, and Bantaran. Adherents experience differences in calculations because it is based on the Old Javanese calender and is influential on Islamic holidays. Of course it is different from the calculation of the Hijri calender. Aboge Muslims do not mind these differences in calculations. The existence of Aboge Muslims until now is still a lot because they consider it a legacy from their ancestors. The spirit in religious activities is also different, of course. The purpose of this study was to determine whwther there were changes in the religious activities of Aboge Muslims during the pandemic in Probolinggo Regency. Using qualitative research methods because they are appropriate and suitable for analyzing phenomena. Herbert Mead’s theory of action explains action, in the form of religious activities of Aboge Muslims during the Covid-19 pandemic in Probolinggo Regency. The results of this study stated that there is no significant difference in religious activities before and during the pandemic. The implementation of religious activities is carried out with enthusiasm and the intention has not decreased to worship amid the Covid-19 pandemic.Keywords : Islam Aboge, religious activities, pandemic Penganut Islam Aboge (Alip Rebo Wage) banyak terdapat di Kabupaten Probolinggo, meliputi Kecamatan Leces, Tegalsiwalan, Dringu, dan Bantaran. Penganutnya mengalami perbedaan dalam perhitungan karena didasarkan pada kalender Jawa Kuno dan berpengaruh pada hari besar Islam. Tentunya berbeda dengan perhitungan kalender Hijriyah. Penganut Islam Aboge tidak mempermasalahkan perbedaan perhitungan tersebut. Eksistensi penganut Islam Aboge sampai sekarang masih banyak karena mereka menganggap sebagai warisan leluhur. Semangat dalam kegiatan keagamaan juga berbeda pastinya. Tujuan dilakukannya penelitian ini untuk mengetahui apakah terdapat perubahan pada kegiatan keagamaan penganut Islam Aboge pada masa pandemi di Kabupaten Probolinggo. Menggunakan metode penelitian kualitatif karena tepat dan sesuai untuk melakukan analisis fenomena. Teori tindakan Herbert Mead menjelaskan tentang tindakan, berupa kegiatan keagamaan penganut Islam Aboge pada masa pandemi COVID-19 di Kabupaten Probolinggo. Hasil penelitian menyatakan tidak terdapat perbedaan yang cukup signifikan pada kegiatan keagamaan sebelum dan saat pandemi. Pelaksanaan kegiatan keagamaan dilaksanakan dengan penuh semangat dan niat tidak mengalami penurunan untuk beribadah ditengah pandemi COVID-19.Kata kunci : Islam Aboge, kegiatan keagamaan, pandemi Covid 19.